INTEGRASI LAPORAN KEUANGAN BERDASARKAN STANDAR AKUNTANSI KEUANGAN EMKM DAN PAJAK PENGHASILAN FINAL MENGGUNAKAN MICROSOFT EXCEL PADA YENI BAKERY - DOMINIKA SIBAGARIANG, EFRY YENI; Iqbal, Johandri; Yuliansyah, Dwi Novrian (Journal of Applied Accounting And Business, 2026)
Preparation of financial statements and fulfillment of tax obligations remain major challenges for Micro, Small, and Medium Enterprises (MSMEs). This study aims to analyze the implementation of SAK EMKM–based financial reporting and its integration with the calculation of Final Income Tax (PPh Final) in accordance with Government Regulation Number 23 of 2018 at Yeni Bakery MSME using Microsoft Excel. The research method employed is descriptive qualitative, using observation and interviews. The results show that prior to system implementation, financial recording was conducted manually and lacked structure. After applying Microsoft Excel based on SAK EMKM, financial records became more systematic and produced complete and accurate financial statements. The integration of Final Income Tax calculation based on gross turnover facilitates the determination of tax obligations and enhances tax compliance. The study concludes that Microsoft Excel is effective as a supporting tool for simple financial recording and reporting for MSMEs.